2018
DOI: 10.5897/ajb2017.16294
|View full text |Cite
|
Sign up to set email alerts
|

Comparative survey of three processes used for the extraction of total phenol content and total flavonoid content of Anacardium occidentale L. and the assessment of its antioxidant activity

Abstract: Three processes were used for the extraction of total phenol and total flavonoid contents of Anacardium occidentale L. and to determine its antioxidant activity. Whatever the extraction process was, the total flavonoid and total phenol contents were of the same order. With the microwave-assisted extraction (MAE), 666.07 mg gallic acid equivalent (GAE)/100 g dry matter (DM) of total phenol content was obtained from the stem barks, 601.71 mg/100 g DM from the leaves and 69.18 mg quercetin equivalent (QE)/100 g D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…This could be attributed to the nutrient content of cashewnut, diet palatability and acceptability by fish. Cashewnuts have been reported to be highly nutritious and contain all the essential amino acids, vitamins and mineral elements (Sogunle et al, 2009;Madjitol-Betoloum et al, 2018). Akande et al (2015) reported significant increases in final weight and weight gain in chicken fed with full fat cashewnut meal based diet with reference to the control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to the nutrient content of cashewnut, diet palatability and acceptability by fish. Cashewnuts have been reported to be highly nutritious and contain all the essential amino acids, vitamins and mineral elements (Sogunle et al, 2009;Madjitol-Betoloum et al, 2018). Akande et al (2015) reported significant increases in final weight and weight gain in chicken fed with full fat cashewnut meal based diet with reference to the control.…”
Section: Resultsmentioning
confidence: 99%
“…Cashew crop is indigenous to Brazil and was introduced to East and West Africa, India and Portuguese in the early 16 th century (Frankel, 1991). The crop is now widely cultivated and distributed worldwide (Akinhanmi et al, 2008, Madjitol-Betoloum et al, 2018. On the global scale, cashew is ranked the third most produced edible nut (Salomon et al,2018) and traded for its nutritional value (John et al,2017).…”
Section: Introductionmentioning
confidence: 99%
“…Another problem is the use of different reference standards and different extraction solvents. Literature data on the content of phenolic compounds of methanolic extract obtained by different methods of extraction from the bark of stem, leaves and cashew nuts of A. occidentale, presented a phenol range from 593.47± 0.05 to 660.07 ± 3.95 mg EAG/100g and flavonoids from 70.39 ± 0.06 to 81.17 ± 1.08 mg EQ/100g (Salomon et al, 2018).…”
Section: Quantification Of Total Phenols and Flavonoidsmentioning
confidence: 99%
“…Resorcinolic acid, ascorbic acid, carotenoids (α-carotene, β-carotene and β-cryptoxantin), vitamin C and phenols are also identified in cashew apples (Farid et al, 2014). The work of Madjitoloum et al (2018b) isolated two flavonoids: quercetin-3-O--D-glucopyranoside and Kempferol-3-O--D-glucopyranoside. The decoction and infusion of the leaves and bark of the trunk are used in pharmacopoeia to treat several diseases namely: High blood pressure, gastrointestinal ailments, ulcers, and sore throat (Jeansheng and Cheng, 2018).…”
Section: Introductionmentioning
confidence: 99%